ANCIENT VIETNAMESE WORDS IN SOUTHERN FOLK SONG COLLECTIONS PUBLISHED IN THE FIRST HALF OF THE 20th CENTURY - Mai Thi Gia La (Tạp chí Khoa học Đại học Đà Lạt)
The article examines and explains the meanings of archaic Vietnamese words in southern folk song collections published in the late 19th and early 20th centuries. We have identified and selected typical Vietnamese words that are now rarely used or used differently. To explain these words’ meanings in folk songs, we use dictionaries, such as Vietnamese Dictionary, Ancient Vietnamese Vocabulary Dictionary, Đại Nam quốc âm tự vị (Dictionnaire Annamit) – the first Vietnamese dictionary, and Southern Dialect Dictionary. This research outlines a unique and exciting feature of the southern language that was popular in folk songs and people’s lives in the South.